A PROSPECTIVE COMPARATIVE COHORT STUDY: FUNCTIONAL RESULTS OF INTERTROCHANTERIC FEMUR FRACTURES TREATED WITH DYNAMIC HIP SCREW VERSUS PROXIMAL FEMORAL NAIL, BHAGALPUR, INDIA. - Gupta, Kanhaiya Lal (Student's Journal of Health Research Africa, 2024)
Background Dynamic Hip Screw (DHS) and Proximal Femoral Nail (PFN) are two commonly used devices for managing intertrochanteric femur fractures (ITF), each with its advantages and limitations. Understanding their relative efficacy is essential for informed treatment decisions. The study aims to compare the functional outcomes of intertrochanteric femur fractures managed with DHS versus PFN. Methods A prospective comparative cohort study was carried out from July 2021 to July 2023. One hundred participants with ITF were enrolled, with equal distribution between the DHS and PFN treatment groups. Demographic data, fracture classifications, surgical details, functional outcomes, complications, and radiographic assessments were recorded. Statistical analysis was achieved to compare outcomes between the two groups. Results The mean age of participants in the DHS group was 72 years, while in the PFN group, it was 69 years, with no significant difference observed. Fracture classifications and surgical durations were comparable between groups. Functional outcomes, assessed using the Harris Hip Score (HHS) at 3, 6, and 9 months post-surgery, showed similar improvement trends with no significant variation between DHS and PFN groups. Complication rates and rates of radiographic union were also similar. Conclusion Both DHS and PFN fixation techniques demonstrated comparable efficacy in promoting functional recovery and fracture healing for intertrochanteric femur fractures. The choice between the two methods should be based on individual patient factors, fracture characteristics, and surgeon preference. Recommendations Further research should explore long-term outcomes beyond the 9-month follow-up period, including patient-reported quality-of-life measures. Randomized controlled trials with larger sample sizes may provide additional insights into the optimal management of intertrochanteric femur fractures. Surgeons should consider factors such as fracture stability, bone quality, and patient comorbidities when selecting the most appropriate fixation device.